HUBUNGAN INTEGRITAS DAN DISIPLIN DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KOTA SIBOLGA - Riska Apifah; Kaharuddin; Nelly A. Sinaga (CV. ALIM'SPUBLISHING, 2023)
The formulation of the problem in this study is whether Integrity and Discipline have a positive and significant relationship to employee performance at the Secretariat Office of the Regional People's Representative Council (DPRD) of Sibolga City. This study aims to determine the relationship between integrity and discipline on employee performance at the Secretariat Office of the Regional People's Representative Council (DPRD) in Sibolga City. The sample in this study were all employees of the Secretariat of the Regional People's Representative Council (DPRD) of Sibolga City, totaling 39 (thirty nine) people. The type of research used in this research is the survey method, which is the method used to obtain data from certain natural places and the research collects data through observation, distribution of questionnaire documentation and interviews. The data analysis technique in this study is Multiple Linear Regression. The results of the regression analysis with the equation Y = 2.666 + 0.526 X1 + 0.397X2, it can be explained that a constant of 2.666 means that if Integrity (variable X1) and Discipline (variable X2) = 0, then the Performance variable Y = 2.666 and if Integrity (variable X1) and Discipline (variable X2) = 1, then performance (variable Y) = 3.589. From the F test (Simultaneous) or Ftest, Fcount is 21.941 > Ftable 3.259. Therefore Fcount 21.941 > Ftable 3.259, meaning that there is a significant influence between integrity and discipline on performance. So it can be concluded that integrity and significant influence on performance at the Secretariat Office of the Regional People's Representative Council (DPRD) of Sibolga City. Then the results of the F test, the hypothesis that the author examined from this study can be declared accepted. The results of this study indicate: Integrity partially has a positive and significant effect on employee performance; Discipline partially has a positive and significant effect on Employee Performance; Integrity and Discipline partially have a positive and significant effect on Employee Performance